2012
DOI: 10.4047/jap.2012.4.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Complication rates and patient satisfaction with removable dentures

Abstract: PURPOSEThe purpose of this clinical study was to evaluate the frequency and type of prosthetic complications in relation to type and properties of removable dentures and to investigate the influence of these complications and several data about the existing dentures on patient satisfaction.MATERIALS AND METHODSNinety nine patients (44 males and 55 females) wearing removable dentures have been included in the study. The complications of the patients were recorded; patient satisfaction was determined with a Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 37 publications
0
74
0
13
Order By: Relevance
“…The denture has to be constructed so that the border conforms to the shallowest point that the sulcus reflection reaches during normal function. This means that for some of the time when the patient is at rest, the denture will be slightly underextended (1,5). The results of the present study showed that ulceration caused dissatisfaction and difficulties while speaking.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The denture has to be constructed so that the border conforms to the shallowest point that the sulcus reflection reaches during normal function. This means that for some of the time when the patient is at rest, the denture will be slightly underextended (1,5). The results of the present study showed that ulceration caused dissatisfaction and difficulties while speaking.…”
Section: Discussionmentioning
confidence: 62%
“…It should not mechanically traumatize the mucosa, or interfere with the normal function of the tongue, lips and cheeks, thus impairing the retention of the denture, and should not interfere with esthetics or speech (1,48). An overbulked denture base may make it difficult for the cheek muscles to position the food bolus between the teeth, and interfere with lip movement during speech (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to that of Bilhan H who found ulceration in 47 of 99 patients (47.5 %). [4,7,8] Hence, the quality of the prosthetic treatment will affect oral health. This clinical study was designed to collect information about the various complications such as fracture of denture base or other components, the need for relining, the need for repair of artificial teeth, and to evaluate their possible relation with denture type and several properties of the dentures.…”
Section: Section: Dentistry Discussionmentioning
confidence: 99%
“…The main problems that patients encounter after insertion of the removable dentures are loss of retention, ulcers, denture stomatitis, loss of artificial teeth, epulis fissuratum, fractured denture base etc. [4][5][6] Failure of dentures will affect oral health and in turn the quality of life. There are only few studies reported evaluating complications after treatment with removable dentures.…”
Section: Introductionmentioning
confidence: 99%